Cellulose nanocrystal based composites: A review - Shojaeiarani, Jamileh; Bajwa, Dilpreet S; Chanda, Saptaparni (Composites. Part C, Open access, 2021)
•The cellulose nanocrystals (CNC) characterization techniques are presented.•The CNC nanocomposite manufacturing techniques are examined.•Effect of CNCs on the physico-mechanical properties of CNC nanocomposites is highlighted.•Characterization techniques for evaluating CNC nanocomposites are summarized.•Effect of CNCs on the physico-mechanical properties of nanocomposites is highlighted.•Application of CNC in emerging polymer nanocomposites is discussed. Cellulose nanocrystals (CNC) have received much attention as renewable, biodegradable, nontoxic, and low-cost nanomaterials with some remarkable properties. Desirable engineering properties of CNC include large surface to volume ratio, high tensile strength (~10 GPa), high stiffness (~110–130 GPa), and high flexibility. They can be chemically modified to tailor their properties for high-end engineering and biomedical applications. Despite their outstanding properties, the wide-scale application is lacking due to their surface characteristics and processing challenges. To achieve their full potential safer extraction methods, improved surface modification and functionalization methods and processing techniques are being researched. This review attempts to access methods for characterizing CNC, and CNC composites as well as their emerging new applications as smart materials. The review is a valuable resource for researchers and scientists working in industry or academia to provide an update on the use of CNC materials and their composites in packaging, biomedical, and high-efficiency energy systems.